Fatigue Life Analysis Of Car Deck Construction on a Ferry Ro Ro - Amam Baharullah; Achmad Baidowi; Edi Jadmiko (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Fatigue life analysis is often overlooked in ship development, leading to an uncertain understanding of a ship’s construction lifespan. This study focuses on the fatigue life of the car deck, which is affected by deformation on a ro-ro ferry. The research aims to determine the maximum stress, location, the cause of deformation, and the fatigue life of the car deck on a ro-ro passenger ship. The calculations assess the car deck’s lifespan and provide a reference for future design considerations. Finite element analysis (FEA) is used, with fatigue life calculated using the Sonderberg method. The research begins with calculating the ship’s weight and buoyancy distribution, then determining the ship’s longitudinal strength from the load distribution. The analysis reveals that the highest stress occurs under hogging wave conditions, exceeding the yield strength of 321 MPa. Specifically, at overload and hogging wave conditions, the highest stress of 486.1 MPa is found on the starboard side between longitudinal stiffeners 1 and 2 (900 mm from the centerline), between frames 56 and 57, with a fatigue life of 4.3 years.